Comparative study of outcomes of type 1 tympanoplasty with and without anterior tucking - Thingujam, Sonee; Poduval, Jayita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Type-1 tympanoplasty is the functional restoration of the normal middle ear by repairing the tympanic membrane (TM). Different techniques are still evolving to devise a way to give optimal graft uptake and hearing improvement with minimal instrumentation. Various studies have been done to assess the role of anterior tucking in type-1 tympanoplasty and to assess its superiority over other methods in repairing subtotal perforations and large perforations involving the anterior quadrant. Methods: This study was done to compare the outcomes of endoscopic type-1 tympanoplasty with and without anterior tucking. 60 cases of chronic otitis media (COM) mucosal type were divided into 2 groups of 30 patients each. Group 1 underwent endoscopic type-1 tympanoplasty with anterior tucking and group 2 underwent endoscopic type-1 tympanoplasty without anterior tucking. The outcomes were evaluated after 6 months and compared in terms of graft uptake and hearing gain. Results: The mean air-bone gap improvement was 13.16±2.65 in group 1 and 12.90±3.78 in group 2, which had statistically insignificant differences indicating similar hearing outcomes in both the groups. 96.7% successful graft uptake was achieved in group 1 and 90% in group 2, showing statistically insignificant differences indicating similar graft uptake rates in both the groups. Conclusions: Anterior tucking with endoscopic type-1 tympanoplasty could provide good graft support and efficient hearing improvement but cannot be labelled as a mandatory step in repairing subtotal perforations or large perforations involving anterior quadrant as the outcomes are comparable to the endoscopic type-1 tympanoplasty done without anterior tucking.